Flow Cytometry of Human Primary Epidermal and Follicular Keratinocytes - Gragnani, Alfredo (Open Science Company, LLC, 2008)
Objective: The aim of this study was to characterize using flow cytometry cultured human primary keratinocytes isolated from the epidermis and hair follicles by different methods. Methods: Human keratinocytes derived from discarded fragments of total skin and scalp hair follicles from patients who underwent plastic surgery in the Plastic Surgery Division at UNIFESP were used. The epidermal keratinocytes were isolated by using 3 different methods: the standard method, upon exposure to trypsin for 30 minutes; the second, by treatment with dispase for 18 hours and with trypsin for 10 minutes; and the third, by treatment with dispase for 18 hours and with trypsin for 30 minutes. Follicular keratinocytes were isolated using the standard method. Results: On comparing the group treated with dispase for 18 hours and with trypsin for 10 minutes with the group treated with dispase for 18 hours and with trypsin for 30 minutes, it was observed that the first group presented the largest number of viable cells, the smallest number of cells in late apoptosis and necrosis with statistical significance, and no difference in apoptosis. When we compared the group treated with dispase for 18 hours and with trypsin for 10 minutes with the group treated with trypsin, the first group presented the largest number of viable cells, the smallest number of cells in apoptosis with statistical significance, and no difference in late apoptosis and necrosis. When we compared the results of the group treated with dispase for 18 hours and with trypsin for 10 minutes with the results for follical isolation, there was a statistical difference in apoptosis and viable cells. Conclusion: The isolation method of treatment with dispase for 18 hours and with trypsin for 10 minutes produced the largest number of viable cells and the smallest number of cells in apoptosis/necrosis.